Sex misinformation of teachers in the public elementary schools of Caloocan City and their implications to health education - Mendoza, Evelina Menez 1938- (1972)
This paper determined sex misinformation among teachers in the public elementary schools in the West District of Caloocan City. In general, the elementary school teachers revealed a high percentage of acceptance of some of the sex misinformation items in the inventory administered to them.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Teachers -- Caloocan City; Health education -- Caloocan City; Sex instruction